A preparation method and application of Prussian blue analog material
By using transition metal salts of organic ligands to react with sodium ferrocyanide in the preparation of sodium ion battery positive electrode materials, the transition metal ions are slowly released, which solves the problems of slow kinetics and structural collapse of the sodium ion battery positive electrode materials, and achieves efficient electrochemical performance improvement and cost reduction.
Patent Information
- Application Number
- CN202310533596.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-05-12
AI Technical Summary
The existing sodium ion battery positive electrode materials have slow kinetics during the insertion and deintercalation process, and the reversible specific capacity of the material is low, which has structural collapse problems, which affects the cycling performance and rate performance of the battery.
The transition metal salt of organic ligand reacts with sodium ferrocyanide, and by slowly releasing transition metal ions, the nucleation rate and crystal growth rate are reduced, the Fe(CN)6 vacancies and crystal water content are reduced, and the Prussian blue analog materials with low defects, high crystallization and low moisture content are prepared.
It significantly improves the cycle life and rate performance of sodium ion batteries, maintains the structural stability of the material, reduces production costs, and improves the long-term stability of the battery.
Smart Images

Figure CN116534871B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries and relates to a preparation method of a Prussian blue analog material and application thereof. Background Art
[0002] With the rapid development of the economy, human society's demand for energy continues to increase, and the non-renewable nature of fossil energy makes the development of renewable energy imminent. Since renewable energy sources such as solar energy, wind energy, and tidal energy are intermittent in time and discontinuous in space, it is necessary to develop large-scale static energy storage technology to change these current situations and enable continuous and stable energy output. Lithium-ion batteries have the advantages of high specific capacity, high voltage platform, and good cycle performance and have been successfully put into commercial use. However, lithium resources are limited and unevenly distributed around the world. Most of my country's lithium resources rely mainly on imports, which increases the cost of lithium batteries. In the long run, it cannot meet the demand for large-scale energy storage. Compared with lithium, sodium is abundant in global reserves, and sodium and lithium are in the same main group, which makes sodium-ion batteries and lithium-ion batteries have many common physical and chemical properties and similar working principles. Therefore, the development of high-performance, low-cost new sodium-ion battery cathode materials has become a hot topic in academic research.
[0003] In recent years, many metal framework materials such as transition metal layered oxides and polyanion compounds have been widely studied as positive electrode materials for sodium ion batteries. However, the strong binding force of sodium ions in tightly packed oxides makes their insertion and deinsertion kinetics relatively slow. The heavier molar weight (X = P, S, As, Si, etc.) in polyanion compounds makes the reversible specific capacity of the materials low (≤120 mAh g -1 Prussian blue analogs and their derivatives, referred to as PBAs, have a molecular formula of Na x M[Fe(CN)6] y□1-y zH2O (M = Fe, Co, Ni, Mn, Cu, Zn and other transition metals). Due to its three-dimensional open skeleton and two-electron redox capacity (up to 170 mAh g -1 ), fast embedding kinetics, easy synthesis and low production cost have attracted the attention of researchers.
[0004] PBAs can usually be prepared by coprecipitation of transition metal ions and hexacyanoferrate anions. Studies have shown that the electrochemical properties of PBAs are closely related to their inherent crystal structure. In traditional coprecipitation reactions, due to the rapid reaction rate, vacancies are generated and coordinated water occupies a large amount of Fe(CN)6 crystal framework, resulting in the actual chemical formula of Prussian blue being Na 2-x M[Fe(CN)6] y□1-y·zH2O, where □ represents Fe(CN)6 vacancies. The presence of vacancies will reduce the electrochemical performance of the battery. The main reason is that Fe(CN)6 vacancies will cause charge imbalance, reduce the content of Na in the lattice, and introduce more water into the framework, thereby reducing the initial charge capacity. Secondly, crystal water may react with Na + Competition for accommodation space will block Na + In addition, the randomly distributed Fe(CN)6 vacancies make the framework of PBAs + The insertion and extraction reactions of PBAs lead to structural collapse, thus reducing the battery life. Therefore, it is particularly important to reduce the nucleation rate and control the content of crystal water and vacancy defects during the synthesis of PBAs to improve the storage capacity of PBAs. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a preparation method and application of a Prussian blue analogue material. By adopting a transition metal salt of an organic ligand to react with sodium ferrocyanide, the transition metal salt of the organic ligand slowly releases transition metal ions during the reaction process, thereby slowing down the nucleation rate and the excessively fast precipitation reaction, solving the problem of a large number of crystal defects and coordinated water in the structure of PBAs, and preparing a Prussian blue analogue material with low defects, high crystallinity and low water content, thereby effectively alleviating the phenomenon of poor cycle performance and rate performance in sodium ion batteries.
[0006] The present invention is achieved through the following technical scheme: a Prussian blue analog material and a preparation method and application thereof, wherein the preparation method comprises the following steps:
[0007] S1. Under an inert gas atmosphere, dissolving soluble sodium ferrocyanide in deionized water to obtain solution A;
[0008] S2. Under an inert gas atmosphere, dissolving a transition metal salt of an organic ligand in deionized water to obtain a solution B;
[0009] S3, water is deoxygenated by passing inert gas to obtain deoxygenated water;
[0010] S4. Under magnetic stirring, the A and B solutions are simultaneously added dropwise into deoxygenated water using a peristaltic pump, and co-precipitation, centrifugal washing and vacuum drying are performed in sequence to obtain a Prussian blue analog material.
[0011] Preferably, the Prussian blue analog material and preparation method thereof are characterized in that the soluble sodium ferrocyanide in step S1 comprises: sodium ferrocyanide, sodium ferrocyanide decahydrate, or a combination of both.
[0012] Preferably, the Prussian blue analog material and the preparation method thereof are characterized in that the inert gas atmosphere in step S1 comprises any one of helium, argon and nitrogen.
[0013] Preferably, the Prussian blue analog material and the preparation method thereof are characterized in that the transition metal salt of the organic ligand described in step S2 is an acetylacetonate of a transition metal, including any one or more combinations of manganese acetylacetonate, iron acetylacetonate, molybdenum acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate, zinc acetylacetonate, and beryllium acetylacetonate.
[0014] Preferably, the Prussian blue analog material and the preparation method thereof are characterized in that, in step S4, the dosage relationship between solution A and solution B satisfies that the molar ratio of Fe to transition metal salt is 1:1-1.5.
[0015] Preferably, the Prussian blue analog material and preparation method thereof are characterized in that the rotation speed of the magnetic stirring in step S4 is 100-1000 rpm.
[0016] Preferably, the Prussian blue analog material and preparation method thereof are characterized in that the rate of dropwise addition by the peristaltic pump in step S4 is 0.1-10 ml / min.
[0017] Preferably, the A and B solutions are added dropwise into the deoxygenated water using peristaltic pump a and peristaltic pump b respectively, wherein the dropping rate of peristaltic pump a is faster than that of peristaltic pump b.
[0018] More preferably, the dripping acceleration rate of peristaltic pump a is 1-8 ml / min; the dripping acceleration rate of peristaltic pump b is 0.5-5 ml / min.
[0019] The inventors found that the dripping rate of sodium ferrocyanide per unit time is faster than that of the transition metal salt of the organic ligand, which can control the amount of contact between the two per unit time, avoid excessive reaction rate, reduce the exposure and generation probability of PBA vacancies during co-precipitation, reduce the amount of coordinated water generated, and improve the electrochemical performance of the battery.
[0020] The dropping acceleration rate of sodium ferrocyanide can be 2-5 times of the dropping acceleration rate of the organic ligand transition metal salt, that is, the dropping acceleration rate of peristaltic pump a is 2-5 times of the dropping acceleration rate of peristaltic pump b.
[0021] In the embodiment of the present invention, the drip acceleration rate of the peristaltic pump a is 2-3 times the drip acceleration rate of the peristaltic pump b.
[0022] Preferably, the Prussian blue analog material and preparation method thereof are characterized in that the co-precipitation in step S4 refers to standing and aging at 25-60° C. for 5-36 hours.
[0023] Preferably, a pre-precipitation reaction is carried out before the co-precipitation, and the pre-precipitation refers to standing and aging at 5-15° C. for 4-10 hours.
[0024] The present invention first pre-precipitates at low temperature, the reaction process is slow and controllable, the generation of vacancies and crystal water is reduced, and then the temperature is increased for co-precipitation. By controlling the temperature, a small amount of Fe(CN)6 vacancies that have been generated can be induced to have a regular arrangement. Therefore, the generation of randomly distributed Fe(CN)6 vacancies can be fundamentally suppressed, the stability of the PBAs framework can be maintained, and the long-term stability of the battery can be improved.
[0025] Preferably, the Prussian blue analog material and the preparation method thereof are characterized in that the washing solvent in step S4 is one or a combination of deionized water and ethanol.
[0026] Preferably, the Prussian blue analog material and preparation method thereof are characterized in that the vacuum drying temperature in step S4 is 80-200° C. High temperature vacuum drying is beneficial to maintaining the structural stability of the PBAs framework.
[0027] The invention provides a Prussian blue analog material with low defects, high crystallinity and low water content, which is prepared by adopting the preparation method.
[0028] The invention also provides use of the Prussian blue analog material as an electrode material.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention optimizes the preparation process, selects a transition metal salt containing an organic ligand to react with sodium ferrocyanide, and the transition metal salt of the organic ligand slowly releases transition metal ions in the solution, thereby reducing the nucleation rate of the coprecipitation reaction and delaying the crystal growth, so that the prepared Prussian blue and its analogues have lower Fe(CN)6 vacancies and lower crystal water content, high crystallinity, complete structure, and high mechanical strength. The application of the Prussian blue and its analogues in the positive electrode material of the sodium ion battery significantly improves the cycle life and rate performance of the sodium ion battery, and has broad application prospects.
[0031] 2. The present invention adopts low-temperature pre-precipitation to reduce the probability of Fe(CN)6 vacancies while inducing a regular arrangement of a small amount of Fe(CN)6 vacancies, which can fundamentally inhibit the generation of randomly distributed Fe(CN)6 vacancies, maintain the stability of the PBAs framework, and help improve the long-term stability of the battery.
[0032] 3. The present invention controls the contact between the raw material transition metal salt and sodium ferrocyanide per unit time, so that the dropping rate of sodium ferrocyanide is faster than that of the transition metal salt of the organic ligand, thereby avoiding excessive reaction rate, reducing the probability of generating PBA vacancies during the coprecipitation process, reducing the generation of coordinated water, and improving the electrochemical performance of the battery.
[0033] 4. The present invention has a simple preparation process, a short cycle, and can be prepared in large quantities. Since no auxiliary reagents such as chelating agents are required during the preparation process, the production cost is greatly reduced, and the invention has low energy consumption, is green and pollution-free, and exhibits environmentally friendly characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron microscope (SEM) image of the Mn-Fe based Prussian blue analog electrode material Mn(acac)2 prepared in Example 1;
[0035] Figure 2 This is a scanning electron microscope (SEM) image of the Mn-Fe based Prussian blue analog electrode material EDTAMnNa2 prepared in Comparative Example 1;
[0036] Figure 3 This is a scanning electron microscope (SEM) image of the Mn-Fe-based Prussian blue analog electrode material Mn(AC)2-NaCl prepared by adding high concentration of sodium chloride in the conventional method in Comparative Example 2;
[0037] Figure 4 This is a scanning electron microscope (SEM) image of the Mn-Fe-based Prussian blue analog electrode material Mn(AC)2-Na-cita prepared by adding high concentration sodium citrate using the traditional method in Comparative Example 3;
[0038] Figure 5 Transmission electron microscope (TEM) image of Mn(acac)2, a Mn-Fe based Prussian blue analog electrode material prepared in Example 1;
[0039] Figure 6 The X-ray diffraction (XRD) patterns of Example 1 and Comparative Examples 1, 2, and 3 are shown;
[0040] Figure 7 The Fourier transform infrared (FT-IR) spectra of Example 1 and Comparative Examples 1, 2, and 3 are shown;
[0041] Figure 8 Thermogravimetric (TG) analysis diagrams of Example 1 and Comparative Examples 1, 2, and 3;
[0042] Fig. 9 The performance diagram of the cycle stability of the battery assembled with the Mn-Fe based Prussian blue obtained in Example 1 and Comparative Examples 1, 2, and 3 as the positive electrode of the sodium ion battery at a rate of 2.0C;
[0043] Fig.10 The figure is a rate performance diagram of a battery assembled using the Mn-Fe-based Prussian blue obtained in Example 1 and Comparative Examples 1, 2, and 3 as the positive electrode of a sodium ion battery at 0.1C, 0.5C, 1.0C, 2.0C, 5.0C, and 10.0C. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Obviously, the embodiments described below are only part of the embodiments disclosed by the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the protection scope disclosed by the present invention.
[0045] Example 1
[0046] A Mn-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0047] S1. Under N2 atmosphere, dissolve sodium ferrocyanide decahydrate in deionized water to obtain 60 ml, 0.02 mmol / ml solution A;
[0048] S2. Under N2 atmosphere, dissolve manganese acetylacetonate in deionized water to obtain 60 ml, 0.02 mmol / ml solution B;
[0049] S3, take 60 ml of deionized water, pass N2 to remove dissolved oxygen, and obtain 60 ml of deionized water marked as C;
[0050] S4. At room temperature and under magnetic stirring, add solution A and solution B into solution C at a rate of 1 ml / min using peristaltic pumps a and b respectively. After the addition is completed, cool to 10°C and let stand for 8 h, then heat to 35°C and let stand for 36 h. Wash with deionized water and ethanol by centrifugation and dry in vacuo at 100°C to obtain the Mn-Fe-based Prussian blue analogue Mn(acac)2.
[0051] Example 2
[0052] A Co-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0053] S1. Under N2 atmosphere, dissolve sodium ferrocyanide decahydrate in deionized water to obtain 60 ml of 0.02 mmol / ml solution A;
[0054] S2. Under N2 atmosphere, dissolve cobalt acetylacetonate in deionized water to obtain 60 ml of 0.02 mmol / ml solution B;
[0055] S3, take 60 ml of deionized water, pass N2 dissolved oxygen into it, and obtain 60 ml of deoxygenated deionized water, marked as C;
[0056] S4. At room temperature and under magnetic stirring, add solution A and solution B into solution C at a rate of 1 ml / min using peristaltic pumps a and b respectively. After the addition is completed, cool to 6°C and let stand for 10 h, then heat to 40°C and let stand for 28 h. Wash with deionized water and ethanol by centrifugation and dry in 100°C in vacuum to obtain a Co-Fe-based Prussian blue analogue.
[0057] Example 3
[0058] A Fe-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0059] S1. Under N2 atmosphere, dissolve sodium ferrocyanide decahydrate in deionized water to obtain 60 ml, 0.02 mmol / ml solution A;
[0060] S2. Under N2 atmosphere, dissolve ferric acetylacetonate in deionized water to obtain 60 ml, 0.02 mmol / ml solution B;
[0061] S3, take 60 ml of deionized water, pass N2 dissolved oxygen into it, and obtain 60 ml of deoxygenated deionized water, marked as C;
[0062] S4. At room temperature, under magnetic stirring, add solution A and solution B into solution C at 2 ml / min using peristaltic pumps a and b respectively. After the addition, cool to 12°C and let stand for 8 h, then heat to 35°C and let stand for 30 h. Wash with deionized water and ethanol by centrifugation and dry in 130°C under vacuum to obtain an Fe-Fe-based Prussian blue analogue.
[0063] Example 4
[0064] A Ni-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0065] S1. Under N2 atmosphere, dissolve sodium ferrocyanide decahydrate in deionized water to obtain 60 ml, 0.02 mmol / ml solution A;
[0066] S2. Under N2 atmosphere, dissolve nickel acetylacetonate in deionized water to obtain 60 ml, 0.02 mmol / ml solution B;
[0067] S3, take 60 ml of deionized water, pass N2 dissolved oxygen into it, and obtain 60 ml of deoxygenated deionized water, marked as C;
[0068] S4. At room temperature and under magnetic stirring, add solution A and solution B into solution C at a rate of 1 ml / min using peristaltic pumps a and b respectively. After the addition is completed, cool to 15°C and let stand for 8 hours, then heat to 42°C and let stand for 24 hours. Wash with deionized water and ethanol by centrifugation and dry in 100°C in vacuum to obtain a Ni-Fe-based Prussian blue analogue.
[0069] Example 5
[0070] A Cu-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0071] S1. Under N2 atmosphere, dissolve sodium ferrocyanide decahydrate in deionized water to obtain 60 ml, 0.02 mmol / ml solution A;
[0072] S2. Under N2 atmosphere, dissolve copper acetylacetonate in deionized water to obtain 60 ml, 0.02 mmol / ml solution B;
[0073] S3, take 60 ml of deionized water, pass N2 dissolved oxygen into it, and obtain 60 ml of deoxygenated deionized water, marked as C;
[0074] S4. At room temperature and under magnetic stirring, add solution A and solution B into solution C at a rate of 1 ml / min using peristaltic pumps a and b respectively. After the addition is completed, cool to 15°C and let stand for 10 h, then heat to 48°C and let stand for 24 h. Wash with deionized water and ethanol by centrifugation and dry in 120°C in vacuum to obtain a Cu-Fe-based Prussian blue analogue.
[0075] Example 6
[0076] A Mn-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0077] Steps S1-S3 are the same as those in Example 1;
[0078] S4. At room temperature and under magnetic stirring, solution A was added dropwise to C at 2 ml / min using a peristaltic pump a, and solution B was added dropwise to C at 1 ml / min using a peristaltic pump b. After the addition was completed, the temperature was lowered to 10°C and allowed to stand for 8 h, then raised to 35°C and allowed to stand for 36 h. The mixture was washed with deionized water and ethanol by centrifugation and dried in 100°C in vacuum to obtain a Mn-Fe-based Prussian blue analogue Mn(acac)2.
[0079] Example 7
[0080] A Co-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0081] Steps S1-S3 are the same as those in Example 2;
[0082] S4. At room temperature and under magnetic stirring, solution A was added dropwise to solution C at a rate of 4 ml / min using a peristaltic pump a, and solution B was added dropwise to solution C at a rate of 2 ml / min using a peristaltic pump b. After the addition was completed, the temperature was lowered to 6°C and allowed to stand for 10 h, then raised to 40°C and allowed to stand for 28 h. The mixture was washed with deionized water and ethanol by centrifugation and dried in 100°C in a vacuum to obtain a Co-Fe-based Prussian blue analogue.
[0083] Example 8
[0084] A Ni-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0085] Steps S1-S3 are the same as those in Example 4;
[0086] S4. At room temperature and under magnetic stirring, add solution A to C at 3 ml / min using peristaltic pump a, and at the same time add solution B to C at 1 ml / min using peristaltic pump b. After the addition is completed, cool to 15°C and let stand for 8 h, then heat to 42°C and let stand for 24 h. Wash with deionized water and ethanol by centrifugation and dry in 100°C in vacuum to obtain a Ni-Fe-based Prussian blue analogue.
[0087] Example 9
[0088] A Mn-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0089] Steps S1-S3 are the same as those in Example 1;
[0090] S4. At room temperature and under magnetic stirring, solution A was added dropwise to C at a rate of 1 ml / min using a peristaltic pump a, and solution B was added dropwise to C at a rate of 2 ml / min using a peristaltic pump b. After the addition was completed, the temperature was lowered to 10°C and allowed to stand for 8 h, then raised to 35°C and allowed to stand for 36 h. The mixture was washed with deionized water and ethanol by centrifugation and dried in 100°C in a vacuum to obtain a Mn-Fe-based Prussian blue analogue, Mn(acac)2.
[0091] Example 10
[0092] A Mn-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0093] S1. Under N2 atmosphere, dissolve sodium ferrocyanide decahydrate in deionized water to obtain 60 ml, 0.02 mmol / ml solution A;
[0094] S2. Under N2 atmosphere, dissolve manganese acetylacetonate in deionized water to obtain 60 ml, 0.02 mmol / ml solution B;
[0095] S3, take 60 ml of deionized water, pass N2 dissolved oxygen into it, and obtain 60 ml of deoxygenated deionized water, marked as C;
[0096] S4. At room temperature and under magnetic stirring, add solution A and solution B into solution C at a rate of 1 ml / min using peristaltic pumps a and b respectively. After the addition is completed, let it stand at 35°C for 36 hours, wash it with deionized water and ethanol by centrifugation, and dry it in vacuum at 100°C to obtain the Mn-Fe-based Prussian blue analogue Mn(acac)2.
[0097] Embodiment 11
[0098] A Co-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0099] Steps S1-S3 are the same as those in Example 2;
[0100] Step S1S4, under magnetic stirring at room temperature, add solution A and solution B to solution C at a rate of 1 ml / min using peristaltic pumps a and b respectively. After the addition is completed, let it stand at 40°C for 28 hours, wash it with deionized water and ethanol by centrifugation, and dry it in vacuo at 100°C to obtain a Co-Fe-based Prussian blue analogue.
[0101] Comparative Example 1
[0102] A Mn-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0103] S1. Dissolve sodium ferrocyanide decahydrate in deionized water to obtain 60 ml of 0.02 mmol / ml solution A;
[0104] S2, dissolving disodium manganese ethylenediaminetetraacetate in deionized water to obtain 60 ml of 0.02 mmol / ml solution B;
[0105] S3, take 60 ml of deionized water, pass N2 to remove dissolved oxygen, and obtain 60 ml of deionized water marked as C;
[0106] S4. Under magnetic stirring, add solutions A and B into C using a peristaltic pump at 1 ml / min. After the addition is completed, add 30 ml of 0.1 M ascorbic acid dropwise, then age at room temperature (about 25°C) for 12 h, wash with deionized water and ethanol by centrifugation, and dry in vacuo at 100°C to obtain the Mn-Fe-based Prussian blue analogue EDTAMnNa2.
[0107] Comparative Example 2
[0108] A Mn-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0109] S1. Add sodium ferrocyanide decahydrate into 60 ml of deionized water and dissolve it by magnetic stirring to prepare a 0.02 mmol / ml solution A;
[0110] S2, dissolving and dispersing manganese acetate tetrahydrate in 60 ml of deionized water under magnetic stirring to prepare a 0.02 mmol / ml solution B;
[0111] S3, take 60 ml of deionized water, add NaCl, and prepare 0.2 mol / ml solution C;
[0112] S4. Under magnetic stirring, add solutions A and B into C using a peristaltic pump at 1 ml / min, and age them at room temperature (about 25°C) for 6 h, wash them with deionized water and ethanol by centrifugation, and dry them in vacuo at 100°C to obtain a Mn-Fe-based Prussian blue analogue Mn(AC)2-NaCl.
[0113] Comparative Example 3
[0114] A Mn-Fe based Prussian blue analog electrode material, the specific preparation method comprises the following steps:
[0115] S1. Dissolve sodium ferrocyanide decahydrate in deionized water to obtain 60 ml of 0.02 mmol / ml solution A;
[0116] S2, dissolving manganese acetate tetrahydrate in deionized water to obtain 60 ml, 0.02 mmol / ml solution B;
[0117] S3, sodium citrate dihydrate was dissolved in deionized water to obtain 60 ml, 0.2 mol / ml solution C;
[0118] S4. Under magnetic stirring, add solutions A and B into C using a peristaltic pump at 1 ml / min, and age them at room temperature (about 25°C) for 6 h, wash them with deionized water and ethanol by centrifugation, and dry them in vacuo at 100°C to obtain the Mn-Fe-based Prussian blue analogue Mn(AC)2-Na-cita.
[0119] Performance Testing
[0120] The following embodiments and comparative examples involve the assembly and testing of sodium ion batteries: the preparation of the positive electrode material of the sodium ion battery is to grind the Prussian blue analogue and the conductive carbon in the following embodiment with a binder in a mass ratio of 7:2:1, add an appropriate amount of N-methylpyrrolidone to make a slurry, apply it on an aluminum foil current collector with a scraper, and use it as the positive electrode of the sodium ion battery after drying and slicing; the diaphragm used for the sodium ion battery is glass fiber, model GF / C; the electrolyte used is PC+5% FEC; metallic sodium is used for the negative electrode; the electrochemical performance of the assembled sodium ion battery is tested at room temperature (about 25°C) using a blue battery test system (voltage range is 2.0-4.0V), and the results are shown in Table 1.
[0121] Table 1
[0122]
[0123] Depend on Figure 1-5 (SEM Figure 1 , 2, 3, 4 and TEM images), it can be seen that compared with comparative examples 1-3, the morphology and particle size of Mn(acac)2 prepared in Example 1 of the present invention are more uniform, presenting a cubic morphology of about 1-2 μm and fewer structural defects. Figure 6 From the XRD patterns of Example 1 and Comparative Examples 1-3, it can be seen that the Prussian blue analogue Mn(acac)2 synthesized by organic ligand transition metal and EDTAMnNa2 prepared in Comparative Example 1 have a cubic phase, while the Prussian blue analogue prepared by traditional transition metal salts has a rhombohedral phase. Figure 7 It can be seen from the FT-IR graphs of Example 1 and Comparative Examples 1-3 that the Mn(acac)2 prepared in Example 1 contains relatively low crystal water; Figure 8 Thermogravimetric data analysis of Example 1 and Comparative Examples 1-3 showed that the weight loss at 200°C was the weight loss of water of crystallization. Compared with other preparation methods (Comparative Examples 1-3), the Mn(acac)2 prepared in Example 1 contained less water of crystallization and defects in its structure (weight loss of 8.67%).
[0124] pass Figure 9-10 As can be seen from Table 1, the Prussian blue analogue Mn(acac)2 synthesized by button-type sodium ion organic ligand transition metal assembled as the positive electrode material of sodium ion battery also has more excellent performance. Compared with Comparative Examples 1-3, the rate performance and long cycle stability of Mn(acac)2 prepared in Example 1 are effectively improved.
[0125] Therefore, the present invention adopts a coprecipitation reaction of suitable precursors (transition metal salts containing organic ligands and sodium ferrocyanide), and the transition metal salts of organic ligands slowly release transition metal ions in the solution, thereby reducing the nucleation rate of the coprecipitation reaction and delaying crystal growth, so that the prepared Prussian blue and its analogues have lower Fe(CN)6 vacancies and lower crystal water content, high crystallinity, complete structure and few defects.
[0126] Furthermore, it can be seen from Table 1 that in Example 1 and Example 6, the dripping rate of sodium ferrocyanide per unit time is faster than that of the transition metal salt of the organic ligand, and the first-cycle efficiency and 100-cycle cycle retention rate of the corresponding battery materials are improved to a certain extent, and the electrochemical performance is optimized. If the dripping rates of the two are opposite (Example 9), the first-cycle efficiency and 100-cycle cycle retention rate of the battery material are slightly reduced. Similarly, the experimental data of Examples 2, 7 and Examples 4, 8 also reflect that adjusting the dripping rate of the raw materials and controlling the contact situation per unit time can avoid excessive reaction rate, reduce the probability of PBAs vacancies during co-precipitation, and improve the electrochemical performance of the battery.
[0127] It can be seen from Examples 1 and 10 that the present invention adopts a low-temperature pre-precipitation-co-precipitation method, which can induce a regular arrangement of a small amount of Fe(CN)6 vacancies that have been generated, inhibit the generation of randomly distributed Fe(CN)6 vacancies, maintain the stability of the PBAs framework, and thus the long-term stability data of the battery material can be significantly improved.
[0128] The Prussian blue analog material prepared by the invention has the advantages of low defects, high crystallinity and low water content, and has good application prospects.
[0129] Those skilled in the art should understand that the above embodiments are only for the purpose of clearly illustrating the present disclosure, and are not intended to limit the scope of the present application. For those skilled in the art, other changes or modifications may be made based on the above disclosure, and these changes or modifications are still within the scope of the present invention.
Claims
1. A method for preparing a Prussian blue analog material, characterized in that: The following steps are involved: S1. Under an inert gas atmosphere, dissolving soluble sodium ferrocyanide in deionized water to obtain solution A; S2. Under an inert gas atmosphere, dissolving a transition metal salt of an organic ligand in deionized water to obtain a solution B; S3, water is deoxygenated by passing inert gas to obtain deoxygenated water; S4. Under magnetic stirring, solution A and solution B are simultaneously added dropwise into deoxygenated water, and co-precipitation, centrifugal washing and vacuum drying are performed in sequence to obtain a Prussian blue analog material; The transition metal salt of the organic ligand described in step S2 is an acetylacetonate of a transition metal, including any one or more combinations of manganese acetylacetonate, iron acetylacetonate, molybdenum acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate, zinc acetylacetonate, and beryllium acetylacetonate; In step S4, the A and B solutions are added dropwise into the deoxygenated water by using peristaltic pump a and peristaltic pump b respectively, wherein the dripping acceleration rate of peristaltic pump a is faster than that of peristaltic pump b; the dripping acceleration rate of peristaltic pump a is 1-8 ml / min; the dripping acceleration rate of peristaltic pump b is 0.5-5 ml / min; In step S4, a pre-precipitation reaction is performed before co-precipitation, and the pre-precipitation refers to standing and aging at 5-15° C. for 4-10 hours.
2. The method for preparing the Prussian blue analog material according to claim 1, characterized in that: The soluble sodium ferrocyanide in step S1 includes: one or a combination of sodium ferrocyanide and sodium ferrocyanide decahydrate; the inert gas atmosphere includes: any one of helium, argon and nitrogen.
3. The method for preparing the Prussian blue analog material according to claim 1 or 2, characterized in that: In step S4, the amount of solution A and solution B is such that the molar ratio of Fe to transition metal is 1:1-1.
5.
4. The method for preparing the Prussian blue analog material according to claim 1 or 2, characterized in that: In step S4, the rotation speed of the magnetic stirring is 100-1000 rpm.
5. The method for preparing the Prussian blue analog material according to claim 1 or 2, characterized in that: The drop acceleration rate of peristaltic pump a is 2-5 times that of peristaltic pump b.
6. The method for preparing the Prussian blue analog material according to claim 1 or 2, characterized in that: The co-precipitation in step S4 refers to aging at 25-60°C for 5-36 hours; the vacuum drying temperature is 80-200°C.
7. A Prussian blue analogue material prepared according to the method for preparing a Prussian blue analogue material according to any one of claims 1 to 6.
8. Use of the Prussian blue analog material according to claim 7 as an electrode material.
Citation Information
Patent Citations
Prussian blue-based high-stability high-activity Pt-based catalyst for fuel cell and preparation method thereof
CN104485464A
Preparation method of iron-catalyzed phosphazene compound
CN109762017A